The State of food and agriculture 1979 - Food and Agriculture Organisation of the United Nations (Rome Food and Agriculture Organisation of the United Nations, 1980)
The United Nations Second Development Decade is drawing to a close with a record of some achievements but many disappointments. In ,food and agriculture, the rate of growth of production in the developing world has averaged about 3 percent ayear in the 1970s a quartet- less than the target rate of 4 percent set for the Decade. While a score of developing countries have been able to accelerate their rate of growth to 4 percent or more, the increase in .food production has failed to keep pace with the growth of population in more than half of the developing countries, particularly the poorer ones. The undernourished in the developing market economies are at least 420 million and continue to increase in number.
lje 28/06/17
Loans
Keywords: Food production; Agriculture; Forestry; Trade; Rurl developmet